2022
DOI: 10.1038/s41598-022-20641-6
|View full text |Cite
|
Sign up to set email alerts
|

Autologous matrix induced chondrogenesis (AMIC) as revision procedure for failed AMIC in recurrent symptomatic osteochondral defects of the talus

Abstract: Autologous matrix induced chondrogenesis (AMIC) is a bone marrow stimulating technique used for the surgical management of chondral defects of the talus. The present study evaluated the clinical outcomes and imaging of AMIC as revision procedure for failed AMIC surgery for osteochondral defects of the talus. Forty-eight patients with symptomatic osteochondral defects who received a revision AMIC were evaluated after a minimum of two years follow-up. Patients with previous procedures rather than AMIC, those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Behrens first introduced AMIC into OLT surgery in 2005 [16]. In the past few decades, some studies have reported that the AMIC technique has shown satisfactory results in treating primary OLT, secondary OLT (after initial surgical failure) and OLT with subchondral bone cysts [17][18][19][20]. Recently, several studies have integrated AMIC with autogenous bone grafting, particularly for the concurrent presence of subchondral cysts.…”
Section: Introductionmentioning
confidence: 99%
“…Behrens first introduced AMIC into OLT surgery in 2005 [16]. In the past few decades, some studies have reported that the AMIC technique has shown satisfactory results in treating primary OLT, secondary OLT (after initial surgical failure) and OLT with subchondral bone cysts [17][18][19][20]. Recently, several studies have integrated AMIC with autogenous bone grafting, particularly for the concurrent presence of subchondral cysts.…”
Section: Introductionmentioning
confidence: 99%